(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of laparoscopic hysterectomy for uterine fibroids at Hanoi Obstetrics and Gynecology Hospital. Methods: A retrospective descriptive study was conducted on 130 patients diagnosed with benign uterine fibroids who underwent laparoscopic hysterectomy (total or subtotal) at Hanoi Obstetrics and Gynecology Hospital between January 1, 2024 and December 31, 2024. Results: The mean operative time was 81.33 ± 14.62 minutes, and the mean intraoperative blood loss was 181.34 ± 40.88 mL, with 75.4% of patients losing 100–200 mL of blood. The intraoperative complication rate was 2.3%, and the postoperative complication rate was 1.5%. Postoperatively, 96.9% of patients had no fever, and 91.5% were discharged within 3–5 days. Intraoperative blood loss was significantly associated with a history of abdominal surgery (p = 0.016), largest fibroid diameter, and operative time (p < 0.001). Conclusion: Laparoscopic hysterectomy for uterine fibroids is a safe and effective procedure with low complication rates and rapid postoperative recovery, consistent with the current trend toward minimally invasive gynecologic surgery.